Pojęcie kultury w teorii zarządzania - Sójka, Jacek (Człowiek i Społeczeństwo, 2014)
The aim of this article is to explore the way the notion of culture has been presented in management theories. In some instances, the concept was absent; but a closer inspection can reveal that culture was an issue or a challenge for managers – as it was the case with taylorism, which actually tried to overcome the cultural differentiation of the workforce. Today, intercultural management and the concept of organizational culture are a crucial part of management theory and education. But the abundance of books and articles on the impact of culture on the economy poses yet another challenge for the students of culture. Is this phenomenon understood correctly, and does intercultural management do justice to the nature of culture and intercultural relations? Perhaps the focus on culture has been blown out of proportion, and perhaps it is meant to hide a purely technocratic attitude toward the workforce? Nevertheless, it would be hard to understand globalization without taking into account the transcultural phenomen of today’s management.